Implementation of Problem Based Learning Assisted by Excel Virtual Laboratory to Enhance Students' Conceptual Understanding of Reaction Equation Subject - Putri Rahmadani; Ibnu Khaldun; Sri Winarni; Putri Nabilah (Universitas Syiah Kuala, 2026)
The limitations of chemistry laboratory facilities in schools, as well as students' low motivation and conceptual understanding of reaction equation subject, necessitate the implementation of an innovative, technology-assisted learning model. This study aims to apply a problem-based learning (PBL) model assisted by an excel-based virtual laboratory (ChemRec) and to test its effectiveness in enhancing learning motivation and understanding of the concept of reaction equations. The research employed a quasi-experimental design with a non-equivalent control group design. The research subjects were tenth-grade students of SMAN 1 Bandar, divided into an experimental class (n=26) and a control class (n=27). The experimental class received PBL instruction assisted by ChemRec, while the control class received conventional instruction. The research instruments consisted of an ARCS model learning motivation questionnaire (20 items) and a conceptual understanding test (15 multiple-choice questions) which met the validity criteria (r calculated > 0.361) and reliability criteria (Cronbach's alpha = 0.858 > 0.70). Data analysis used the Wilcoxon signed-rank test, the Mann-Whitney U test, and N-Gain. The results showed that the application of ChemRec-assisted PBL significantly increased students' learning motivation (p=0.000 < 0.05) with an average N-Gain of 0.58 (moderate category). All 26 students in the experimental class experienced an increase in learning motivation. The average posttest score of the experimental class (89.23) was higher than that of the control class (75.80) with p < 0.001. The application of the excel-based virtual laboratory-assisted PBL is effective in increasing students' learning motivation and understanding of the concept of reaction equations, and serves as an alternative solution for schools with limited chemistry laboratory facilities